Induction of apoptosis in A549 cells in vitro by Boesenbergin A isolated from Boesenbergia rotunda - Mohd Isa, Norbaiti (2013)
Boesenbergin A (BA) is a chalcone isolated from Boesenbergia rotunda, containing methoxyl and hydroxyl groups in its structure. These groups have been reported to exert anti-proliferative, antioxidant and anti-inflammation activities. However, there has been no literature reported on the biological activities of BA and its effects on lung cancer. The current in vitro study was designed to investigate the apoptotic induction of BA in A549 cells, as well as its antioxidant and anti-inflammatory activities. Human hepatocellular carcinoma cell (HepG2), human prostate cancer cell (PC3), colon adenocarcinoma cell (HT-29), non-small cell lung cancer cell (A549) and normal hepatic cells (WRL-68) were used to evaluate the cytotoxicity of BA using the 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT)assay. The antioxidant activity of BA was assessed by the Oxygen Radical Absorbance Capacity (ORAC) assay and compared to quercetin as a standard reference antioxidant. The anti-inflammatory assay was performed by inducing murine monocytic macrophage cell line (RAW 264.7) using 100 U/mL of interferon-γ (IFN-γ) and 5 μg/mL of lipopolysaccharide (LPS) with or without the presence of BA, and compared concurrently to L-Nitro-Arginine Methyl Ester (L-NAME) as positive control. The production of nitric oxide (NO) after inducing the inflammation was then assessed using Griess reaction. Multiparametric High Content Screening (HCS) assay was conducted to detect changes in total nuclear intensity (chromatin condensation and fragmentation), cell permeability, mitochondrial membrane potential and release of cytochrome c. Caspase assay for caspase-8, -9 and -3/7 were analyzed using luminescence reader, whereas DNA fragmentation was detected through gel electrophoresis. To measure the production of intracellular ROS, 2′,7′-dichlorofluorescin diacetate (DCFH-DA) was used. Cell cycle analysis was performed using Flow Cytometer. Expression of Bax, Bcl2 and Hsp70 protein were detected by using the western blot analysis. Toxic effect of BA on different cell types, reported as IC50, yielded 20.22 ± 3.15, 10.69 ± 2.64, 20.31 ± 1.34, 94.10 ± 1.19, and 9.324 ± 0.24 μg/mL for A549, PC3, HepG2, HT-29 and WRL-68, respectively. ORAC results are reported as the equivalent concentration of trolox that produces the same level of antioxidant activity as the samples tested at 20μg/mL. BA displayed low antioxidant activity, when the results of ORAC assay were reported as trolox equivalents, where BA (20 μg/mL) and quercetin (5 μg/mL) were equivalent to a trolox concentration of 11.91 ± 0.23 and 160.97 ± 0.02 μM, respectively. For the anti-inflammatory assay, the results clearly showed a concentration-dependent decrease in NO production in the induced RAW 264.7 cells, with a significantly low level being evident even at 25 and 50 μM of BA concentrations, with a level of 29.69 ± 2.5 and 25.69 ± 2.0 μM of NO production respectively. The anti-inflammatory activity of BA was significant between concentration of 25 μM to 50 μM but with no significant cytotoxicity towards RAW 264.7 cells at 50 μM. The anti cancer activities of BA was investigated using A549 cell line, as BA was found to be cytotoxic to A549 cells (IC50< 30 μg/mL). The HCS results showed the BA-induced A549 cells exhibited a concentration-dependent increase in total nuclear intensity, cell permeability and cytochrome c release, whereas the cells mitochondrial membrane potential was decreasing (p<0.05), (p<0.01). Luminescence assay for caspase-8, -9 and -3/7 revealed an elevation of all three caspases in concentration-dependent manner (p<0.05). A549 cells treated with BA showed DNA fragmentation at the concentration of 20 and 50 μg/mL of BA. Production of ROS was also elevated in a concentration-dependent manner, indicated by the increase of DCF fluorescence intensity in treated cells (p<0.05). Protein analysis by western blot showed an increase of Bax, whilst Bcl2 and Hsp70 protein were subsequently decreased due to time-dependent treatment (p<0.05). Cell cycle analysis by flow cytometer showed a significant concentration-dependent increase in the sub G1 phase (p<0.05). A slight increase of cell arrest was observed in S phase but it was not statistically significant (p>0.05), which confirmed cell cycle arrest was not induced in treated A549 cells. Collectively, results presented in this study demonstrate that BA inhibited the proliferation of non-small lung cancer in vitro, leading to a possible induction of apoptosis, which was later confirmed to be induced through the extrinsic and intrinsic pathways. Moreover the role of free radicals was significantly found to be elevated with concomitant decrease in Hsp70. This compound also showed low antioxidant capacity and significant anti-inflammatory activity. BA can be a potential drug to treat lung cancer and inflammation.